1992
DOI: 10.1055/s-2006-961498
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cytoprotective Anti-Ulcerogenic Actions of Hydroxychalcones in Rats

Abstract: The preventive effects of hydroxychalcone derivatives on ulcer formation induced by severe necrotizing agents such as 60% ethanol in 150 mM HCl (HCl-ethanol) and 0.2 N NaOH in rats were examined. Among the compounds tested, 2',4'-dihydroxychalcone gave the strongest activity in both experimental models and protected the gastric mucosa from the insult of either necrotizing agent at oral doses ranging from 1 to 10 mg/kg, as evidenced by a dose-related reduction in the ulcer index. The mucosal protective activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 2 publications
(2 reference statements)
0
18
0
Order By: Relevance
“…It is also well known that prostaglandins synthetized in large quantities by the gastrointestinal mucosa can prevent experimentally induced ulcers by ulcerogens. Thus, when the ulcers lesions are induced by indomethacin, the cytoprotective effect of the anti-ulcer agent can be mediated through endogeneous prostaglandins (Yamamoto et al, 1998). The results obtained show that the ulcer surface area and the mean ulcer index were significantly reduced, while the mucus weight increased in the aqueous and methanol extracts treated groups, compared to their respective controls.…”
Section: Discussionmentioning
confidence: 84%
“…It is also well known that prostaglandins synthetized in large quantities by the gastrointestinal mucosa can prevent experimentally induced ulcers by ulcerogens. Thus, when the ulcers lesions are induced by indomethacin, the cytoprotective effect of the anti-ulcer agent can be mediated through endogeneous prostaglandins (Yamamoto et al, 1998). The results obtained show that the ulcer surface area and the mean ulcer index were significantly reduced, while the mucus weight increased in the aqueous and methanol extracts treated groups, compared to their respective controls.…”
Section: Discussionmentioning
confidence: 84%
“…It can be thought that the cytoprotective effect of the extract results from the enhancement of the mucosal barrier through the increase production of prostanglandin. Yamamoto et al (1992) and Tan et al (2000) have shown the prostaglandin-like cytoprotective action of some hydroxychalcone and methylene chloride extract of Bidens pilosa respectively and the methanol leaf extract of A. africana might be producing its antiulcer effects through the same mechanism. The anti-ulcer effects of the methanol extract of the leaves of Aspilia africana may be due to the presence of triterpenes in the extract.…”
Section: Pylorus Ligated-induced Ulcermentioning
confidence: 99%
“…It is also well known that prostaglandins synthesized in large quantities by the gastrointestinal mucosa can prevent experimentally induced ulcers by ulcerogens. Thus, when the ulcer lesions are induced by absolute ethanol or indomethacin, the cytoprotective effect of the antiulcer agent can mediated through endogeneous prostaglandins (Yamamoto et al, 1992). Therefore, it can be thought that HWE may stimulate the secretion of prostaglandin or possess prostaglandin like substances.…”
Section: Discussionmentioning
confidence: 99%